Effect of the added weight on the rear wheels and inflating pressure in agricultural Tractor type (New Holland 2WD) on the performance of Mold Board Plow in terms of some mechanical & physical properties of the soil - Khorshid, Fawzy F. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Experiment was conducted in one fields of Agricultural Sciences College in Sulaymaniyah University with Silty-clay soil in order to study the effect of different weights added to the rear wheels for agricultural tractor type New Holland 2WD, with the effect of pressure bloating of rear wheels on the performance of triple Mold Board in terms of some properties represented by: The amount of fuel consumption, plowing practical speed, Slippage percent, soil penetration resistance, covered soil volume, number of clods which have a diameter more than 10 cm. Split- plot design used in this research under randomized complete block design RCBD, where added weights factor on rear wheels wear put in the main plots represented by two levels which are without weights and added weights by 100 kg per each rear wheel, While bloating pressure factor of the wheels has been developed in sub plots by three levels included 80, 100 and 120 Kpa. The results showed that the added weight had a significant effect on all studded properties except of fuel consumed amount. While bloating pressure factor of the wheels was significantly difference in the level 80 Kpa on 100 Kpa level, which in turn significantly differs on the third level 120 Kpa in all studied properties. As to the interaction between the factors, the weights 200 kg factor with bulging pressure wheels 80Kpa recorded best significant effect on the rest of interactions in all studded properties except in fuel consumed property which the differences between the factors was In favor for the factor without weights with the bulging pressure wheels 80 Kpa, as the results showed that there is no significant differences between number of interactions for all studded properties in the experiment except soil penetration resistance property, where was significant differences between its levels.
Keywords: Added weights to the wheelsWheels bulge pressureMechanical PropertiesSoil Physical PropertiesTriple Mold Board Plow